2022
DOI: 10.3390/sym14102170
|View full text |Cite
|
Sign up to set email alerts
|

Marly Soft Rocks: Correlation of Physical and Mechanical Properties—Examples from Dalmatia (Croatia) and Budapest (Hungary)

Abstract: Soft rocks in various forms of marly materials have an important role in the geological structure of Dalmatia (Croatia) and Budapest region (Hungary). These materials can cause serious problems in design and construction, due to their complex behavior under atmospheric conditions. For the purpose of better understanding soft rocks behavior and their properties, a database with approximately 600 samples collected throughout Dalmatia was made and collated along with 260 samples from the Budapest area. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…A large number of field investigations, geotechnical tests, and engineering construction practices have consistently demonstrated that hard soil and soft rock exhibit characteristics such as expansion and contraction, multiple fractures, and overconsolidation. Furthermore, these materials are prone to displaying engineering properties of low strength, substantial deformation, and susceptibility to softening and becoming muddy upon contact with water [4][5][6][7]. The presence of hard soil and soft rock can create favorable conditions for the occurrence of geological hazards as well as pose challenges in terms of engineering geology [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of field investigations, geotechnical tests, and engineering construction practices have consistently demonstrated that hard soil and soft rock exhibit characteristics such as expansion and contraction, multiple fractures, and overconsolidation. Furthermore, these materials are prone to displaying engineering properties of low strength, substantial deformation, and susceptibility to softening and becoming muddy upon contact with water [4][5][6][7]. The presence of hard soil and soft rock can create favorable conditions for the occurrence of geological hazards as well as pose challenges in terms of engineering geology [8][9][10].…”
Section: Introductionmentioning
confidence: 99%